Age of first exposure to tackle football and chronic traumatic encephalopathy. Issue 5 (27th June 2018) - Alosco, Michael L.; Mez, Jesse; Tripodis, Yorghos; Kiernan, Patrick T.; Abdolmohammadi, Bobak; Murphy, Lauren; Kowall, Neil W.; Stein, Thor D.; Huber, Bertrand Russell; Goldstein, Lee E.; Cantu, Robert C.; Katz, Douglas I.; et al.
Abstract : Objective: To examine the effect of age of first exposure to tackle football on chronic traumatic encephalopathy (CTE) pathological severity and age of neurobehavioral symptom onset in tackle football players with neuropathologically confirmed CTE. Methods: The sample included 246 tackle football players who donated their brains for neuropathological examination. Two hundred eleven were diagnosed with CTE (126 of 211 were without comorbid neurodegenerative diseases), and 35 were without CTE. Informant interviews ascertained age of first exposure and age of cognitive and behavioral/mood symptom onset. Results: Analyses accounted for decade and duration of play. Age of exposure was not associated with CTE pathological severity, or Alzheimer's disease or Lewy body pathology. In the 211 participants with CTE, every 1 year younger participants began to play tackle football predicted earlier reported cognitive symptom onset by 2.44 years ( p  < 0.0001) and behavioral/mood symptoms by 2.50 years ( p  < 0.0001). Age of exposure before 12 predicted earlier cognitive ( p  < 0.0001) and behavioral/mood ( p  < 0.0001) symptom onset by 13.39 and 13.28 years, respectively. In participants with dementia, younger age of exposure corresponded to earlier functional impairment onset. Similar effects were observed in the 126 CTE‐only participants. Effect sizes were comparable in participants without CTE. Interpretation: In this sample of deceased tackle football players, younger age of exposure to tackle football was not associated with CTE pathological severity, but predicted earlier neurobehavioral symptom onset. Youth exposure to tackle football may reduce resiliency to late‐life neuropathology. These findings may not generalize to the broader tackle football population, and informant‐report may have affected the accuracy of the estimated effects. Ann Neurol 2018;83:886–901